Seasonal and Year Wise Variations of Water Quality Parameters in the Dhanmondi Lake, Dhaka, Bangladesh: Seasonal Quality Variations of Dhanmondi Lake Water (Biological Sciences - PJSIR, 2010)
The quality of the surface water through 16 physicochemical variables was monitored at three sites of Dharmondi Lake of Dhaka, Bangladesh, over 5 years during 2002-2007. The concentration of heavy metals (Pb, Cd, Cr, 3- 2Co, Ni, Cu) was below detection limits with few exceptions. No clear seasonal variation trend for Fe, Mn, Zn, PO4 , SO4 , Cl- and F- was observed which differed from year to year. Slight increasing tendency in case of sulphate, phosphate, chloride concentrations and electrical conductivity was observed but it was not clear in other parameters. The levels of all parameters were found well below the standards for drinking water.